2010
DOI: 10.1186/1475-2875-9-106
|View full text |Cite
|
Sign up to set email alerts
|

Anopheles culicifacies breeding in brackish waters in Sri Lanka and implications for malaria control

Abstract: BackgroundAnopheles culicifacies is the major vector of both falciparum and vivax malaria in Sri Lanka, while Anopheles subpictus and certain other species function as secondary vectors. In Sri Lanka, An. culicifacies is present as a species complex consisting of species B and E, while An. subpictus exists as a complex of species A-D. The freshwater breeding habit of An. culicifacies is well established. In order to further characterize the breeding sites of the major malaria vectors in Sri Lanka, a limited la… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
49
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 45 publications
(54 citation statements)
references
References 22 publications
5
49
0
Order By: Relevance
“…culicifacies s . l ., the major malaria vector in Sri Lanka, is recognized as a fresh water mosquito, it has been recently reported to undergo pre-imaginal development in brackish water of up to 4 ppt in eastern Sri Lanka [17]. The present findings show that this is also the case in the northern Jaffna district in Sri Lanka.…”
Section: Discussionsupporting
confidence: 77%
“…culicifacies s . l ., the major malaria vector in Sri Lanka, is recognized as a fresh water mosquito, it has been recently reported to undergo pre-imaginal development in brackish water of up to 4 ppt in eastern Sri Lanka [17]. The present findings show that this is also the case in the northern Jaffna district in Sri Lanka.…”
Section: Discussionsupporting
confidence: 77%
“…The bionomics and ecology of the species within this complex have been largely studied in India [23,241,251] and Sri Lanka [99,252,253], but there is a general lack of detailed information from other regions, especially the western areas [8]. Four species of the complex (A, C, D, E) are reportedly malaria vectors in India where they are apparently responsible for transmitting 60-65% of all cases of malaria in peri-urban and urban environments [254].…”
Section: Resultsmentioning
confidence: 99%
“…culicifacies E was identified for the first time in this study and was confirmed by molecular methods. This species is a highly competent vector for malaria globally and in India (Subbarao et al 1980(Subbarao et al , 1988Jude et al 2010).…”
Section: Discussionmentioning
confidence: 99%
“…culicifacies E has adapted to breed in diverse types of habitats such as brackish water in Sri Lanka like An. culicifacies B (Jude et al 2010). Its adaptability has enabled An.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation